The effect of openings on the performance of self-compacting concrete with volcanic pumice powder and different steel fibers. (December 2022) - Abdullah, Gamil M.S.; Alshaikh, Ibrahim M.H.; M. Zeyad, Abdullah; Magbool, Hassan M.; Bakar, B.H. Abu
Abstract: This study primarily aims at investigating the impact of incorporating volcanic pumice powder (VPP), with different steel fibers on self-compacting concrete (SCC) beams' performance with a circular opening of a diameter of 20 mm at the centroid. To this end, twenty-one SCCs opened beams (100 mm × 100 mm × 500 mm); together with/without steel fiber, were cast and examined by employing the test of center-point bending. For this study, five different types of fiber and various aspect ratios, involving the hook-end fiber type of (60–30 mm), the straight fiber type of (21–13 mm), as well as the flat-end fiber type of (six varying concrete mixtures made by adding 1% of a volume fraction), were examined. At a replacement rate of 30% of the cement mass, VPP has been incorporated into the mixture. The experimental test results confirmed the performance improvement in deflection, a failure load, and a failure mode due to the existence of steel fibers in the examined concrete matrix. The presence of steel fibers has significantly increased the ultimate loads with a range of the gain ratio of 11–49% compared with solid beams (i.e., SCC beams). Accordingly, the fibers were able to offset the drawbacks, which were triggered by the opening. Moreover, this study demonstrated the possibility of benefiting from industrial wastes, such as VPP to reduce the use of cement and manufacture of SCC.